Eco-consciousness in Shakya's Soch [Thought] - Wagle, Anupa (JODEM: Journal of Language and Literature, 2024)
This article aims at analyzing thought-provoking essays collection, Soch [Thought] by Karna Shakya highlighting environmental issues and eco awareness found in it. So, the article investigates the ecological issues and the sense of consciousness to protect existing environment while conducting developmental and economic activities. The article analyses what ecological issues are used and how they prioritise the preservative mindset of the writer to protect environment in future. To address these objectives, ecocritical perspective is used mainly the idea of sustainable development. The significance of this study is to contribute to the reader to see the essay collection as a serious message to maintain the balance between economy and ecology. The paper concludes that Soch is full of positive thoughts to preserve ecology during economic activities. It paved the way towards eco-awareness through Nepali literature to address contemporary environmental issues faced by not only Nepal but the world.